Visible-light-driven photocyclization reaction: photocatalyst-free mediated intramolecular N–N coupling for the synthesis of 2H-indazole-3-carboxamides from aryl azides. Issue 19 (27th July 2021) - Liu, Jinni; Liu, Na; Yang, Qingqing; Wang, Long
Abstract : A visible-light-driven photocyclization reaction of aryl azides to access 2 H -indazole-3-carboxamides in moderate to excellent yields has been realized efficiently under photocatalyst-free and external additive-free conditions. Abstract : In this report, a visible-light-driven photocyclization reaction of aryl azides to access 2 H -indazole-3-carboxamides in moderate to excellent yields has been realized efficiently under photocatalyst-free and external additive-free conditions. An N–N bond coupling was achieved for this N-atom incorporation transformation using an aryl azide as the N-atom source. The transformation of the aryl azide by photocyclization was also achieved under sunlight irradiation. Additionally, this protocol, as a green and sustainable process, possesses some advantages such as broad substrate scope, step- and atom-economy, environmental friendliness and mild reaction conditions.